Literary Psychological Analysis of the Novel entitled “Laut Bercerita” by Leila S. Chudori - Alya Selsa Meyriska (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: Literary work contains meaning in it, not just a form of work that contains aesthetics. Poetry means imaginative literary works, the words used are arranged using aesthetic and simple words, readers who do not have the knowledge of analyzing poetry will have difficulty understanding the meaning of the poetry they read. The writer is interested in analyzing the poem